S85 The effects of exposure to IL-9 alone or in combination with IL-13 on the mucociliary differentiation of bronchial epithelial cells from normal and asthmatic children. (16th November 2010) - Parker, J C; Thavagnanam, S T; Skibinski, G; Shields, M D; Heaney, L G
Abstract : Background: IL-9 is a pleiotropic Th2 cytokine that has been implicated in the pathogenesis of asthma. IL-9 has been linked to goblet cell hyperplasia and decreased ciliogenesis in animal models and an epithelial injury model in adults. We tested the effects of IL-9 alone and in combination with IL-13, an important cytokine in allergic asthma, during differentiation of bronchial epithelial cells from both asthmatic and normal children. Hypothesis: We hypothesised that bronchial epithelial cells from normal children exposed to IL-9 would result in goblet cell hyperplasia and decreased ciliogenesis, with additional augmented response when treated with a combination of IL-9 and IL-13. Methods: We cultured bronchial epithelial cells from asthmatic and normal children at an air–liquid interface for 28 days. We enumerated the presence of goblet and ciliated cells at the end of the experimental period. Results: IL-9 stimulation alone did not alter goblet cell numbers in differentiating cultures from normal or asthmatic children. IL-9 stimulated PBECs from normal children had reduced ciliated cell numbers and increased MUC5AC secretion at the apical surface which was not seen in asthmatic cells. Combining IL-9 and IL-13 had no additional synergistic effect. Conclusions: We conclude that IL-9 alone or in combination with IL-13 did not stimulate goblet cell hyperplasia in bronchial epithelial cells cultures from normal children. We have shown that it is does lower the number of ciliated cells during differentiation of PBECs from normal children however this effect is not seen in cells from asthmatic children.